Splenectomy reduces lung metastases and tumoral and metastatic niche inflammation - Stöth, Manuel; Freire Valls, Aida; Chen, Mingyi; Hidding, Sarah; Knipper, Karl; Shen, Ying; Klose, Johannes; Ulrich, Alexis; Ruiz de Almodóvar, Carmen; Schneider, Martin; Schmidt, Thomas (International journal of cancer, 2019)
The immune microenvironment plays a crucial role in supporting tumor growth and metastasis. Tumor-associated macrophages (TAMs) and neutrophils (TANs) are essential components of this microenvironment and affect tumor growth and progression in almost all solid neoplasms. Furthermore, TAMs, TANs and tumor-infiltrating dendritic cells (TIDCs) are found to infiltrate specific distant organs to prepare them as a site for metastatic cell seeding, forming the pre-metastatic niche. The spleen was identified as a major reservoir and source of circulating and tumor infiltrating immune cells. However, discrepancies about its role in supporting tumor growth exist. Thus, here we investigated the role of splenectomy in primary tumor and metastatic growth, and in the formation of an inflammatory niche. In a murine 4T1 and E0771 breast and Panc02 pancreatic cancer model, our results show that while splenectomy reduces the number of infiltrating TAMs, TANs and TIDCs within primary tumors, it does not affect its growth. In line, fewer TAMs, TANs and TIDCs accumulate in the metastatic microenvironment after splenectomy. Interestingly though, this affected metastatic growth depending on the metastatic route/site. The number of hematogenous breast cancer lung metastases was reduced after splenectomy but no effect was observed in breast or pancreatic lymph node metastases. Moreover, we observed that the immune composition of the pre-metastatic niche in lungs of breast cancer bearing mice was altered, and that this could cause the reduction of metastases. Altogether, our results highlight that splenectomy affects the immune microenvironment not only of primary tumors but also of pre-metastatic and metastatic sites.
Gesehen am 01.10.2019